2017
DOI: 10.1136/thoraxjnl-2016-209806
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning for patients with chronic respiratory diseases: a systematic review of preferences and practices

Abstract: CRD42016039787.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
125
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 43 publications
3
125
1
Order By: Relevance
“…Conversely, the expectation of ACP causing discomfort to either the patient or their relatives was more commonly cited as a block on having these discussions. This is similar to a previous review of healthcare professional practice which identified concern about taking away patient's hope (Jabbarian et al, ). Whether this is accurate or whether healthcare professionals use this fear of causing distress as an excuse for avoiding ACP is not possible to ascertain from survey research alone.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Conversely, the expectation of ACP causing discomfort to either the patient or their relatives was more commonly cited as a block on having these discussions. This is similar to a previous review of healthcare professional practice which identified concern about taking away patient's hope (Jabbarian et al, ). Whether this is accurate or whether healthcare professionals use this fear of causing distress as an excuse for avoiding ACP is not possible to ascertain from survey research alone.…”
Section: Discussionsupporting
confidence: 87%
“…There is a requirement for greater education and training of nurses, and others, to help them understand both ADs and the ACP process. This has been a frequent recommendation of previous studies and reviews (Jabbarian et al, 2018;Ke et al, 2015;Kermel-Schiffman & Werner, 2017). In particular, it is important for nursing staff to be aware of their legal and professional obligations to protect patients, but also to ensure they do not face punishment themselves.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the goals of the intervention was indeed to have patients understand the prognosis of their disorder and the possible futility of aggressive end-of-life managements. Very little data are available on ACP in COPD; and available data show that ACP is surprisingly uncommon in this population [42-45]. Paradoxically, ACP obtained most often expressed the desire of CPR and maximal treatment, patients failing to acknowledge their prognosis and the natural history of their disease [46].…”
Section: Discussionmentioning
confidence: 99%
“…Jabbarian and colleagues74 performed a systematic review of preferences and practices of ACP in chronic respiratory diseases. They showed that a majority of patients are interested in engaging in ACP, but despite this, ACP is rarely done.…”
Section: Palliative Respiratory Care In Copdmentioning
confidence: 99%